Building Customer Loyalty through Service Quality and Customer Trust - Robby Tanod Mamusung; Andriani Kusumawati; Umar Nimran; Suharyono Suharyono (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Service quality is an important market differentiator and is an instrument that has strong competitiveness. The purpose of this research was to test and to analyze the influence of service quality towards customer trust and customer loyalty, especially in the retail industry. In such an industry, service quality is the key to improve competitiveness. The research was carried out in North Sulawesi with 135 supermarket customer as the sample. The sampling technique was purposive sampling. The research result showed that service quality had significantly positive influence either on the customer trust or customer loyalty. Besides, on the relationship between customer trust and customer loyalty, it also had significant positive finding. Such finding was in line with the concept of SERVQUAL and The Commitment-Trust Theory, stating that service quality interaction would minimize the gap between the expectation and the service received so that it would improve customer trust and eventually they would be back to shop more. The implication of such managerial research was that the supermarket leader in North Sulawesi must focus more and emphasize more on the dimension of service quality especially in terms of reliability, empathy, and warranty. The limitation of this research was the limited area of research, therefore, the area scope should be broader for the next research so that the conceptual model could be generalized.